The 'diaspora advantage' of Pauline Chan (1956–): from multicultural filmmaker to cultural broker. Issue 2 (3rd April 2018) - Yue, Audrey
ABSTRACT: This is the first academic paper to critically introduce and document the 30-year screen career of Pauline Chan, Australia's highest profile Chinese film director, television actress and media producer. Sydney-based, Vietnam-born, Hong Kong-educated and US-trained, Chan has directed six films, starred in 14 and produced four television series and films. Despite her prolific career, there has been no sustained research on her profile and repertoire. This paper evaluates the evolution of Chan's career using the diaspora 'advantage' as a new approach. Characterised by mobility rather than culturalism, the term refers to the benefits brought by and skills of diaspora groups that have allowed them to flourish as transnational actors able to leverage resources in both their countries of origin and settlement. It begins by elaborating how Chan's diaspora advantage has allowed her to challenge welfare multiculturalism and extend aesthetic multiculturalism. It further documents her transition from a multicultural filmmaker to a cultural intermediary by leveraging her diasporic advantage across the film sectors in China and Australia, and opening up new industrial routes outside of the confines of policy. Using interdisciplinary methods to screen biography that include interviews with the filmmaker, film archival research, critical cultural policy studies, and studies in Asian Australian cinema and political economy, this paper argues that the new approach of the diaspora advantage turns the deficit associated with the diaspora into a dividend that has the potential to rethink the imaginary between Asia and Australia.